The Relationship between Organizational Equilibrium and Organizational Happiness: A Field Study Applied to the Egyptian Pharmaceutical Trade Company - Abo Lifa, Sanaa; El-Tahan, Emad (The Arab Journal of Administration, 2021)
The objective of the study: To examine the relationship between the dimensions of Organizational Equilibrium (direct salary, compensation, promotion, development opportunities, achievement, diversity of tasks, employee relationship, and relationship with management) and organizational happiness dimensions (positive emotional impact and satisfying acceptance). Study methodology: The study used the descriptive analytical method. In the field a sample of (350) workers of the Egyptian Pharmaceutical Trade Company, from a population of (4840) workers. The study used the survey list as a means of obtaining data. The hypothesis of the study and its sub-hypotheses were developed. For analysis of data, the study used the statistical package of social science SPSS (25). Study results: The study found a positive relationship with statistical significance between some dimensions of organizational equilibrium and the dimensions of organizational happiness. Administrative applications of the study: Human resources management should Support the social benefits package provided within the company, enhancing promotion systems in the company taking into account the high efficiencies of employees, redesigning workplaces to help increase social interaction, and reviewing the organizational structure of the company by conforming to flat structures.as much as possible.